Effect of reducing dietary protein level on performance responses and some microbiological aspects of broiler chickens under summer environmental conditions. (1st June 2012) - Laudadio, Vito; Dambrosio, Angela; Normanno, Giovanni; Khan, Rifat Ullah; Naz, Shabana; Rowghani, Ebrahim; Tufarelli, Vincenzo
This study examined the effect of different crude protein (CP) levels in the diet on growth performance of broilers as well as the total aerobic mesophilic count (TAMC) and Escherichia coli count (ECC) isolated from chicken faeces. A total 150 day-old broilers (Hubbard) were allocated to three treatments with five replicates containing 10 birds. The dietary treatments consisted of three diets with different CP levels for 42 days: high-protein (HCP, 22.5%), medium-protein (MCP, 20.5%), and low-protein (LCP, 18.5%). Body weight and feed intake were determined and the feed conversion ratio was calculated. Faecal samples were collected at 14, 21 and 42 days. Dietary CP did not affect the growth performance of broilers. Reducing CP level was effective at beneficially modulating the composition of the faecal microflora, in particular TAMC and ECC concentrations (log10 CFU g−1) were significant lower for the LCP birds. During hot temperature conditions (33°C and 70% relative humidity) a low protein diet may help to control the characteristics of the faecal microbial community without negative effects on broiler performance.